Insurgent Groups During Post-Conflict Transformation: The Case of Military Strongmen in Cambodia. Issue 1 (2nd January 2018) - Bultmann, Daniel
Abstract: The article discusses the experiences of a group of military strongmen during the post-conflict transformation of two Cambodian insurgent movements into a society of peace after a decades-long civil war. It explains the reasons why some of these strongmen were able to transfer their high status within the insurgency into senior positions in the incumbent government, while others became impoverished and sometimes even preferred to relapse into further conflict. Even though all of these strongmen shared a very similar life course and fought until the end of the conflict, their post-conflict fates have been very different. Central to the explanation of their behaviour during the transition is their habitus, the set of resources at their disposal and the nature of their vertical and horizontal social networks.